Mineral Composition of Marine Macroalgae from Mandapam Coastal Regions; Southeast Coast of India - G. Karthikaidevi, K. Manivannan, G. Thirumaran; T. Balasubramanian, P. Anantharaman* (Recent Research in Science and Technology, 2010)
The present study focused on the trace metal and mineral composition analysis of various seaweeds such as Chlorophyceae (Cladophora glomerata, Ulva reticulata, Halimeda macroloba, H.tuna), Phaeophyceae (Dictyota dichotoma, Padina pavonica) Rhodophyceae (Gracilaria crassa, Gelidiella acerosa, Hypnea musciformis) collected from Mandapam coastal regions, Southeast coast of India. Among these groups of seaweeds, U. reticulata belonging to the Chlorophyceae showed the maximum contents of mineral elements such as chromium, copper, and magnesium. H.tuna observed the minimum level of mineral content such as cobalt, iron, magnesium, manganese, nickel, lead and zinc.